The fetish of theology: the challenge of the fetish-object to modernity - Dickinson, Colby (Radical theologies and philosophies, 2020)
'By delving into the history of the fetish-object among both modern and contemporary commentators, this book highlights the fetish-object’s role as a philosophical and religious concept of the highest significance. Historically, fetishes are implicated in specific struggles for sovereign (political) and/or religious (hierarchical) power, with their interwoven symbols defined as the primary location for transcendence in our world. This book defines the political consequences of fetish-objects within a western cultural, and primarily theological context through a comparative approach of various literatures on fetish-objects—anthropological to the psychological, Marxist to the theological. It reconceives of fetishes as a form of resistance to oppressive structures, something which motivated Christians themselves historically, and shaped our western understanding of the sacraments far more than has been acknowledged. Taking up this conversation likewise holds forth the possibility of reconceptualizing how fetish-objects and sacramental presences both speak profoundly to our late-modern selves.' --back cover